Pendampingan Ibu dan Anak Prasekolah Dalam Upaya Menjaga Kesehatan Gigi Dan Mulut - Mardhatilla Rachma Primasanti; Amelia Dwi Putri; Mauludiya Nur Hakiki; Riesa Cindi Apriyani; Rikawarastuti Rikawarastuti; Erwin Erwin (Jurnal Inovasi, Pemberdayaan dan Pengabdian Masyarakat, 2023)
Preschool children are a vulnerable group to dental health problems. Education in the preschool age period is essential because children are very easy to learn and direct so children will get used to doing dental health care independently, to get good results this program involves parents. The purpose of this program is to assist mothers and preschool children to maintain dental and oral health. The targets of this activity are preschool students and Ruhul Jihad Kindergarten students in Ciganjur, South Jakarta. The method of implementing the action is conducting dental health education for preschool children and mothers, dental edu visits, and brushing teeth together. The results of the activity showed an increase in knowledge of oral and dental health care for mothers and preschool children, an increase in brushing skills correctly in preschool children, as well as coordinated responses, enthusiasm, and interest in preschool children visiting the dental clinic. The conclusion shows that mentoring activities for mothers and preschool children to maintain dental and oral health are carried out well and provide benefits to the target.